How Children and Adolescents Perceive Their Coping With Home Learning in Times of COVID-19: A Mixed Method Approach - Inga Simm (Frontiers Media S.A., 2021)
With the COVID-19 pandemic, children and adolescents confronted a completely new learning situation. Instead of learning in class, they had to cope with home learning to achieve academically. This mixed-method study examines how children and adolescents in Germany perceive their coping success with home learning during the COVID-19 pandemic and how personal, school, family, and peer context factors relate to this self-perceived coping success. Quantitative data from an online survey of n=141 children (mage=10,8y) and n=266 adolescents (mage=15,2y; study 1) were used to analyze the questions with multiple regression analysis. With the qualitative data from 10 interviews with parents and their children (study 2), we examined the process of how school, family, and peer groups interact with students’ way of coping with home learning. Quantitative data show that most children and adolescents perceived their coping with home learning as successful and that school joy before COVID-19, parental support, and available equipment during home learning are still relevant for children, and family climate, calm place to learn, and equipment during home learning are important for adolescents learning at home. Qualitative data show that students apply individual ways of coping with home learning, where family and peers have a vital role, especially when contact with teachers is limited. Quantitative data confirm the importance of family context for students’ self-perceived coping success.